Description of family characteristics and nutritional status in toddlers - Masturina, Masruroh Luthfiah; Salam, Abdul; Indriasari, Rahayu; Thaha, Abd.Razak; Jafar, Nurhaedar (Universitas Islam Negeri Alauddin Makassar, 2023)
The problem of public health problems caused by malnutrition is one of the main health problems in developing countries which indirectly influences determined by the background of the household or familyThis study aims to describe the characteristics of families and the nutritional status of children aged 24-59 months in the working area of the Malimongan Baru Health Center, Makassar City. This research is a type of descriptive research. The population of this study were all toddlers aged 24-59 months in the Working Area of the Malimongan Baru Health Center. Determination of the sample using the Accidental Sampling technique. The results of the research showed that based on the weight/age indicator there were 53 people (55.8%) underweight, for the height/age indicator there were 50 people (52.6%) stunting and for the wasting weight/height indicator there were 28 people (29.5%). The number of toddlers is more male (50.5%), father's last education is SMA/MA (60.0%), mother's education is SMA/MA (57.9%), most fathers work as laborers (58.9%), mother's work is mostly as housewives (90.5%), family income is in the low category (69.5%), the number of family members under five is >4 people (50.5%), and mother's nutritional knowledge is in the good category (54.7%). In conclusion, the problem of malnutrition in the Working Area of the Malimongan Baru Health Center is categorized as high. Therefore it is necessary to carry out routine monitoring to screen the condition of toddlers so that intervention can be carried out quickly and precisely.